Synthesis, Characterization Of Various Coumarin Derivatives - Jamal M. Hamid (College of Education for Pure Sciences, 2013)
Abstract 3-acetyl coumarin (1) was prepared by reacting salicyldehyde with ethylacetoacetate.3-(2-bromoacetyl coumarin (2) was also prepared by reacting 3-acetyl coumarin with bromine in chloroform solution. Reaction of compound (2) with imidazol in dioxan solution to gave 3-(1H-imidazol-1yl-acetyl) coumarin(3). Compounds (4,5,6) were synthesized by the reaction of compound (3) with hydrazine hydrate, phenyl hydrazine, 2,4-dinitro-phenylhydrazine respectively. Compound (7-15) were synthesized by the reaction of compound (3) with various aromatic and aliphatic amines. The structures of all the synthesized compounds have been established on the basis of physical, spectral )IR, U.V) data. Key words: different coumarin, derived imidazole, schiffbase,phenyl hydrazine coumarin. Introduction